The Association of Parenting and Stunting Status with Children Development Age 12-36 Months in the Work Area of Pauh Health Centre, Padang City - Azrimaidaliza Azrimaidaliza; Fathia Juwita; Zulkarnain Agus (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2021)
ABSTRACT Background: Stunting prevalence is quite high in West Sumatra Province, including Padang City. Parenting factors and nutritional status play a role in children's development.Objective: This study aims to determine the association between parenting and stunting status with the development of children aged 12-36 months.Method: Design study was cross sectional with the population being children aged 12-36 months who lived in the Pauh Public Health Center working area in Padang City with a total sample of 86 children. The sample was taken by using simple random sampling. Data on development of children were collected using KPSP, parenting data by a structured questionnaire, and stunting data through measuring child height. The data is processed by the SPSS program and displayed univariate, bivariate and multivariate data.Results: The results showed that parenting, especially eating patterns and stunting status were related to the development of children aged 12-36 months. The factor most related to the development of children aged 12-36 months is the stunting status of the child (POR = 4.368; 95% CI = 1.781-10.711; p value = 0.001)Conclusion: It should be noted that a balanced diet in accordance with the needs of children in addition to improving health, hygiene and psychosocial parenting mainly for stunting children so that the child's physical growth and development are normal.